KONSEPTUALISASI PENGEMBANGAN MODEL PEMBELAJARAN DEEP-PBL UNTUK MENINGKATKAN PENGETAHUAN DAN SIKAP PEDULI LINGKUNGAN PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI - Putri, Amelia; Permata Ayu, Dewi; Palennari, Muhiddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia is currently one of the countries facing serious environmental issues that have become global concerns, such as pollution and waste accumulation caused by low public awareness of environmental preservation. This condition highlights the need for strategic efforts to foster environmental awareness and pro-environmental behavior from an early age through learning. This study aims to develop the Deep-PBL Learning Model to improve students’ knowledge and environmental care attitudes in biology learning, particularly on the topic of environmental change focusing on waste problems. Deep-PBL is an innovative integration of Problem-Based Learning (PBL) and the Deep Learning approach. The model consists of five learning syntaxes: Awareness (Problem Awareness), Organization (Learning Organization), Investigation (Inquiry), Presentation (Solution Presentation), and Reflection (Reflection and Evaluation). This structure ensures that Deep-PBL not only emphasizes problem solving but also helps students understand the meaning of the learning process and its relevance to real-life contexts. The model encourages students to think critically, reflect on their actions, and internalize values of environmental responsibility so that biology learning does not stop at conceptual mastery, but also develops awareness, empathy, and real commitment in protecting the environment. With its holistic and sustainable nature, Deep-PBL develops cognitive abilities while shaping students’ environmental care attitudes consistently in daily life, thereby having the potential to produce a young generation that is academically competent, environmentally aware, and responsible toward nature.